The Global Attractiveness of the Fixed Point of a Gonosomal Evolution Operator - Absalamov, Akmal T. (Discontinuity, Nonlinearity, and Complexity, 2026)
In the paper we prove a conjecture of U.A. Rozikov and R. Varro about globally attractiveness of a unique nonhyperbolic fixed point of the normalized gonosomal evolution operator of a sex linked inheritance.